N6-methyladenosine-modified circ_0000337 sustains bortezomib resistance in multiple myeloma by regulating DNA repair - Jiang, Siyi; Gao, Lili; Li, Jian; Zhang, Fangrong; Zhang, Yanan; Liu, Jing (Frontiers in Cell and Developmental Biology, 2024)
Studies have shown that bortezomib resistance in multiple myeloma (MM) is mediated by the abnormalities of various molecules and microenvironments. Exploring these resistance mechanisms will improve the therapeutic efficacy of bortezomib. In this study, bone marrow tissues from three patients with MM, both sensitive and resistant to bortezomib, were collected for circRNA highthroughput sequencing analysis. The relationship between circ_0000337, miR-98-5p, and target gene DNA2 was analyzed by luciferase detection and verified by RT-qPCR. We first found that circ_0000337 was significantly upregulated in bortezomib-resistant MM tissues and cells, and overexpression of circ_0000337 could promote bortezomib resistance in MM cells. circ_0000337 may act as a miR-98-5p sponge to upregulate DNA2 expression, regulate DNA damage repair, and induce bortezomib resistance. Furthermore, it was determined that the increased circ_0000337 level in bortezomib-resistant cells was due to an increased N6-methyladenosine (m6A) level, resulting in enhanced RNA stability. In conclusion, the m6A level of circ_0000337 and its regulation may be a new and potential therapeutic target for overcoming bortezomib resistance in MM.